2014
DOI: 10.1162/artl_a_00144
|View full text |Cite
|
Sign up to set email alerts
|

Building Polyhedra by Self-Assembly: Theory and Experiment

Abstract: We investigate the utility of a mathematical framework based on discrete geometry to model biological and synthetic self-assembly. Our primary biological example is the self-assembly of icosahedral viruses; our synthetic example is surface-tension-driven self-folding polyhedra. In both instances, the process of self-assembly is modeled by decomposing the polyhedron into a set of partially formed intermediate states. The set of all intermediates is called the configuration space, pathways of assembly are modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…However, the dodecahedron has 43,380 nets, and, to my surprise and delight, simple heuristics along with our computations revealed the best nets in the lab [4]. Since then our work has evolved into a study of the pathways of self-assembly [3]. This has required some surprisingly sophisticated mathematics.…”
Section: Govind Menonmentioning
confidence: 91%
“…However, the dodecahedron has 43,380 nets, and, to my surprise and delight, simple heuristics along with our computations revealed the best nets in the lab [4]. Since then our work has evolved into a study of the pathways of self-assembly [3]. This has required some surprisingly sophisticated mathematics.…”
Section: Govind Menonmentioning
confidence: 91%
“…In terms of design criteria for capillary self‐folding of polyhedra, Gracias and Menon and coworkers discovered optimal self‐folding nets using a combination of experiments and mathematical analyses . They found that high yielding self‐folding of polyhedra occurs with compact nets with low radius of gyration ( R g ) and with nets featuring high secondary neighbors or vertex connections (secondary panels are those not directly connected by a folding hinge but that can interact with an aligning hinge) .…”
Section: Geometry and Path Design Rulesmentioning
confidence: 99%
“…Importantly, intermediates that were more rigid with fewer degrees of freedom were preferred. Collectively, the unraveling of such rules greatly aids the problem of inverse design of complex structures by self‐folding . The optimal use of nearest neighbors and compact nets can enable defect tolerance and error correction .…”
Section: Geometry and Path Design Rulesmentioning
confidence: 99%
See 2 more Smart Citations